The subject of human being - Haley, Christopher W. (Abingdon, Oxon ; New York, NY : Routledge, 2018)
"The Subject of Human Being presents a sweeping account of the nature of human existence. As a work of philosophical anthropology, the analysis ranges from the basic powers emerging from the mind, to our extraordinary psychological capacities, to the shared sociocultural worlds we inhabit. The book integrates different perspectives on social ontology from a selection of philosophers and theorists, whose advances toward understanding the relationship between individuals and society ought to revolutionize social theory as understood and practiced in the social sciences and humanities. Although grounded in critical realist philosophy of Roy Bhaskar and social theory of Margaret Archer, the book also draws from philosophy of mind, phenomenology of consciousness, psychoanalytic theory, virtue ethics, and personalism to support and extend its arguments. Four elements of human existence are examined: the nature of consciousness, agency, subjectivity, and the social world. Thus, it addresses related issues of power, the agent-structure problem, the formation of beliefs and desires, human universals, and human rights. Portraying a unified social theory that is materialist, realist, dialectical, and centered on emergence, and offering a comprehensive and progressive theory of human being, this book is essential reading for students and scholars of critical realism, philosophy, and the social sciences"--
Philosophical materialism -- The ontology of consciousness -- The ontology of subjectivity -- The subject of psychoanalysis -- The subject of structure -- Social ontology.
OCLC-licensed vendor bibliographic record.
Keywords: Philosophical anthropology; PHILOSOPHY / Movements / Humanism; PHILOSOPHY / General; SOCIAL SCIENCE / Sociology / General